(untitled) (Journal of actual problems of jurisprudence, 2018)
The author examines in his article questions of international criminal law, the prospects are linked to the political integration of the international community in the subject of global criminal policy with universal jurisdiction and able to fundamentally solve the problem of establishing an effective fight against crime. Key words: criminal law, international law, politics, the crime.